(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1915)
The fragments of mediaeval stained glass were found on the top of the vaulting of the south aisle of the nave of Holyrood Abbey Church during repairs to the roof in 1909. They are extremely significant as very little stained glass has survived from mediaeval Scotland. A very brief account of the history and development of mediaeval stained glass is presented and this is followed by a summary of the surviving material in Scotland. At Holyrood there are fragments of glass of two or more of the small lancet windows which at one time existed in the clerestorey on the south side of the nave. One of these windows seems to have belonged to the end of the thirteenth century, another to the beginning of the fourteenth. It is likely that the glass was made in York.